Testing the Effectiveness of the Discovery Learning Model Based on Educational Tourism on Students' Critical and Creative Thinking Abilities - Wahyudin, Didi; Udayani, Ni Wayan Asri; Diza Farhana, Baiq Chunafa; Herianto, Edy; Rachmawati, Retna Ayu; Bin Ziyad, Muhammad Thoriq (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The global transformation in the Industrial Revolution 4.0 era demands students to master 21st-century skills, particularly critical and creative thinking. The low achievement of these skills at the elementary level highlights the need for innovative learning models. This study aims to examine the effectiveness of the edutourism-based Discovery Learning model in enhancing students' critical and creative thinking skills. A quantitative approach with a one-group pretest-posttest design was employed involving 48 fourth-grade students from SDN 1 Terong Tawah. Data were collected through tests and observation sheets, then analyzed using normality tests, Paired Samples T-test, and Effect Size with SPSS 25.0. The results revealed a significant improvement between pretest and posttest scores (sig. 0.037 < 0.05). Although the effect size was small (Cohen’s d = 0.310), these findings confirm that the edutourism-based Discovery Learning model effectively enhances students’ critical and creative thinking skills.